Evidence for overwintering and autochthonous transmission of Usutu virus to wild birds following its redetection in the United Kingdom. Issue 6 (25th October 2022) - Folly, Arran J.; Sewgobind, Sanam; Hernández‐Triana, Luis M.; Mansfield, Karen L.; Lean, Fabian Z. X.; Lawson, Becki; Seilern‐Moy, Katharina; Cunningham, Andrew A.; Spiro, Simon; Wrigglesworth, Ethan; Pearce‐Kelly, Paul; Herdman, Trent; et al.
Abstract: Usutu virus (USUV) is an emerging zoonotic arbovirus in Europe, where it primarily impacts Eurasian blackbirds ( Turdus merula ). For mosquito‐borne viruses to persist in temperate areas, transovarial transmission in vectors or overwintering in either hosts or diapausing vectors must occur to facilitate autochthonous transmission. We undertook surveillance of hosts and vectors in 2021 to elucidate whether USUV had overwintered in the United Kingdom (UK) following its initial detection there in 2020. From 175 dead bird submissions, we detected 1 case of USUV infection, in a blackbird, from which a full USUV genome was derived. Using a molecular clock analysis, we demonstrate that the 2021 detection shared a most recent common ancestor with the 2020 Greater London, UK, USUV sequence. In addition, we identified USUV‐specific neutralizing antibodies in 10 out of 86 serum samples taken from captive birds at the index site, demonstrating in situ cryptic infection and potential sustained transmission. However, from 4966 mosquitoes, we detected no USUV RNA suggesting that prevalence in the vector community was absent or low during sampling. Combined, these results suggest that USUV overwintered in the UK, thus providing empirical evidence for the continued northward expansion of this vector‐borne viral disease. Currently, our detection indicates geographically restricted virus persistence. Further detections over time will be required to demonstrate long‐term establishment. It remains unclear whether the UK, and by extension other high‐latitude regions, can support endemic USUV infection.